Consumer Direction and Choice in Long-Term Care for Older Persons, Including Payments for Informal Care How Can it Help Improve Care Outcomes, Employment and Fiscal Sustainability? - Lundsgaard, Jens (OECD Health Working Papers, 2005)
As the number of older persons in need of long-term care increases, efforts to support older persons remaining in their home are intensified in most OECD countries. In this context of ageing in place, there is a movement towards allowing more individual choice for older persons receiving publicly funded long-term care at home. Having more flexibility in terms of how to receive care can increase the older person's self-determination and that of his/her informal care givers. Having a choice among alternative care providers can empower older persons as consumers and may help strengthen the role of households in the care-management process. Choice can also help address quality aspects that are difficult to quantify but easy to experience for users, such as the personal interaction between the older person and the care giver